Civility behaviour training programme and its influence on staff nurse organisational citizenship: a quasi-experimental study - El-Shahat, Eman Mohamed; Mostafa, Hemat Abdelazem; Shazly, Mona Mostafa (Frontiers in Public Health, 2025)
BackgroundThis study aimed to assess the influence of a civility behaviour training programme on organisational citizenship among nurses in the workplace and to explore various predictors of nurses’ knowledge, workplace civility behaviour, and organisational citizenship behaviour.MethodsIn 2023, a quasi-experimental study (one-group pre-test/post-test) was conducted. A convenience sample of 115 nurses was selected using the intervention method. The study was carried out at El-Sheikh Zayed Specialised Hospital, which is affiliated with the Ministry of Health and Population in Egypt. The self-administered questionnaires included (1) socio-demographic characteristics, (2) a questionnaire assessing nurses’ knowledge about civility behaviour, (3) a questionnaire assessing nurses’ levels of civility perception, and (4) a questionnaire assessing nurses’ levels of organisational citizenship behaviour (OCB) prior to the implementation of the training programme. Statistical analysis was performed using version 25 of SPSS.ResultsA total of 115 nurses were included, with a mean age of 36.24 ± 5.9 years; of them, 59.5% were men, and 55% had 5–10 years of experience. The chi-square test showed highly significant relationships between the citizenship behaviour of nurses and their educational level and attendance at training courses, with p-values <0.01**. Additionally, there were significant correlations between total knowledge, perception related to workplace civility behaviour, and citizenship behaviour at pre-intervention, post-intervention, and at 3 months follow-up. The correlation coefficients indicate strong positive relationships (r = 0.569, r = 0.573, and r = 0.641) between perception and citizenship behaviour pre-intervention, post-intervention, and at the 3-month follow-up intervention, respectively.ConclusionThe implementation of the civility behaviour training programme had a significant positive impact on the organisational citizenship behaviours of the staff nurses. In addition, the majority of staff nurses had a high perception of workplace civil behaviour and citizenship behaviour after the training programme.